Perlindungan Hukum Pekerja yang Terkena Pemutusan Hubungan Kerja di Masa Pandemi Covid-19 - Nazifah Nazifah; Syarifa Mahila (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The Covid-19 pandemic that has hit all countries in the world,including Indonesia, has had a negative impact on Indonesia’s economic growth. The negative impact of this pandemic is that many companies cannot operate properly so that many company suffer losses and not a few are forced to close their companies which  in the end has an impacts on umilateral termination of employment in many companies. The purpose of this study is to analyze the legal protection for workers who experience termination of employment unilaterally during this pandemic, in terms of the perspective of the Manpower Act. The research method used in this research is normative legal method by prioritizing a statutory approach, conceptual approach, and the legal materials used are all laws and regulations related to this research, especially the Manpower Act.Terminations of employment by many companies has a negative impact on workers. Moreover, Article 151Paragraph 1 of Law Number 13 Year 2013 concerning Manpower has emphasized that employers, workers. The Goverment must make every effort to prevent termination of employment, but in Law Number 11 Year 2020 about Job Creation Article 154 Paragraph (1) letter d states that the termination of employment can be carried out in a condition where the company is closed due to force majeure, and this covid-19 pandemic used as a reason for the company’s force majeure to unilaterally lay off workers.  The results of the research are expected to provide legal protection for workers affected by the covid-19 pandemic in the form of unilateral termination of employment.